EFFECT OF WORK EXPERIENCE, INDEPENDENCE, COMPETENCE, PROFESSIONAL CARE DUE AND PROFESSIONAL ETHICS TO AUDIT QUALITY - Gracia Indah Prasetyawati; Bambang Kusdiasmo; Septiana Novita Dewi (ADVANCE, 2018)
This study aims to test and provide empirical evidence that the significance of the influence of work experience, auditor independence, auditor competence, due professional care and professional ethics to audit quality at Public Accounting Firm. The population in this study are auditors working in Surakarta, Yogyakarta and Semarang. The number of samples in this study were 70 people. Sampling was done by Purposive Sampling. The types and sources of data are obtained from primary data sources. The analytical technique used in this study consisted of test instrument research that is the test of validity and reliability test, classical assumption test, multiple linear regression analysis, t test, F test and test R2 . The result of the analysis shows that the work experience and independence of the auditor have a significant positive effect on audit quality, auditor competence, due professional care and professional ethics have no significant positive effect on audit quality. The result of determination coefficient of (R2) is 0,559 or 55,9%. It means that the percentage of donation given by the independent variable is work experience, auditor independency, auditor competence, professional care and professional ethics toward dependent variable that is audit quality (Y) is 55,9%, while the rest 44,1% explained by variable others not analyzed in this study.Keywords: work experience, independence, competence, due professional care, professional ethics and audit quality